Penerapan Latihan Athletic Basic Coordination Terhadap Peningkatan Kemampuan Lari Jarak Pendek Peserta Ekstrakurikuler SMP Negeri 11 Kota Lubuklinggau - Hengki Pramansyah Jaya NH,; Azizil Fikri; Erick Salman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine whether the athletic primary coordination training method affects the increase in short-distance running for extracurricular participants at SMP Negeri 11 Lubuklinggau. This type of quantitative research with a quasi-experimental approach. The population is all extracurricular participants at SMP Negeri 11 Lubuklinggau, and the sampling technique uses a total sampling technique. Data collection was carried out using a test technique in the form of a 60-meter short-distance running test. Based on the results of research and discussion of data on the effect of athletic basic coordination training on increasing the short-distance running ability of extracurricular participants at SMP Negeri 11 Kota Lubuklinggau. The value of tcount is 5.606, and the ttable is 2.26 with a significance of 5% (α = 0.05) with degrees of freedom dk = n-1 where n is the number of student data as many as ten athletes. If the value of tcount > ttable, then the hypothesis is accepted so that the average post-test results of the short-distance running ability of extracurricular participants at SMP Negeri 11 Lubuklinggau City after being given athletic basic coordination training is more than the average pre-test score. In conclusion, there is an effect of the primary coordination athletic training method on the increase in short-distance running in extracurricular participants at SMP Negeri 11 Lubuklingau. Keywords: Athletic Basic Coordination, short-distance running